A review of evidence for food limitation of sponges on Caribbean reefs - Joseph R. Pawlik; Steven E. McMurray; Patrick M. Erwin; Sven Zea (2014)
MEPS Marine Ecology Progress Series Contact the journal Facebook Twitter RSS Mailing List Subscribe to our mailing list via Mailchimp HomeLatest VolumeAbout the JournalEditorsTheme Sections MEPS 519:265-283 (2015) - DOI: https://doi.org/10.3354/meps11093 REVIEW A review of evidence for food limitation of sponges on Caribbean reefs Joseph R. Pawlik1,*, Steven E. McMurray1, Patrick Erwin1, Sven Zea2 1Center for Marine Science and Department of Biology and Marine Biology, University of North Carolina Wilmington, Wilmington, NC 28409, USA 2Universidad Nacional de Colombia, Centro de Estudios en Ciencias del Mar-CECIMAR, Santa Marta, 470006, Colombia *Corresponding author: pawlikj@uncw.edu ABSTRACT: The diversity and biomass of sponges on Caribbean reefs exceeds that of all other benthic organisms. Wilkinson & Cheshire (1990; Mar Ecol Prog Ser 67:285-294) summarized evidence that sponge communities on Caribbean reefs were different from those on the Great Barrier Reef, Australia, reflecting food limitation of the latter, but not of the former. Since then, we have learned much about the ecology of sponges, and the concept of food limitation has recently re-emerged, seemingly without substantive reference to past inter-oceanic comparisons or pioneering studies of sponge physiology. Here, we review the literature in an attempt to correct this digression. Based on current knowledge of sponge nutrition and bottom-up resource gradients (particulate food, dissolved organic carbon [DOC], light, turbulence), we predict 4 patterns of sponge abundance that would suggest food limitation on Caribbean reefs. After a critical review of survey data, correlative studies and manipulative experiments, we can find no evidence for food limitation. Although there is good evidence for higher availability of picoplankton at greater depths, sponge abundance does not mirror this gradient, suggesting that other sources of nutrition are also important, and particulate food is not a limiting factor. Recent studies have renewed interest in the uptake of DOC by both high and low microbial abundance sponge species, suggesting that the absence of bottom-up effects for sponges on Caribbean reefs may be attributable to this mysterious, and likely ubiquitous, food source. The recent unambiguous demonstration of top-down effects of predation on sponge community composition across the Caribbean may owe its clarity to the relative lack of confounding influences of abiotic and bottom-up effects in this study system. KEY WORDS: Bottom-up · Top-down · Food webs · Suspension feeding · Symbiosis · Photoautotrophy · DOC · Benthic–pelagic coupling · Coral reefs · Sponge loop Full text in pdf format See Comment and Reply Comment on this article PreviousCite this article as: Pawlik JR, McMurray SE, Erwin P, Zea S (2015) A review of evidence for food limitation of sponges on Caribbean reefs. Mar Ecol Prog Ser 519:265-283. https://doi.org/10.3354/meps11093 Export citation RSS - Facebook - Tweet - linkedIn Cited by Published in MEPS Vol. 519. Online publication date: January 20, 2015 Print ISSN: 0171-8630; Online ISSN: 1616-1599 Copyright © 2015 Inter-Research.